1993
DOI: 10.1007/bf00168875
|View full text |Cite
|
Sign up to set email alerts
|

Serial evaluation of left ventricular function by radionuclide ventriculography at rest and during exercise after orthotopic heart transplantation

Abstract: Discrepant results have previously been reported concerning long-term left ventricular function in the human transplanted heart as assessed by radionuclide ventriculography. In this study, radionuclide ventriculograms were obtained at rest and during exercise in 19 patients < 6 months, 7-12 months, 13-24 months and > 24 months after transplantation. Ejection fraction decreased significantly from < 6 months to 13-24 months after transplantation (rest: 69.1% +/- 9.7% to 56.7% +/- 8.3%, P < 0.05; exercise: 70.4% … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0
1

Year Published

1994
1994
2010
2010

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(2 citation statements)
references
References 31 publications
0
1
0
1
Order By: Relevance
“…Human transplanted heart provides a good example of cardiac autonomic dysfunction. Some authors have found a significant decrease in left VEF in patients as compared with healthy control subjects (Verani et al ., 1994) or during the long‐term course after heart transplantation (Hartmann et al ., 1993) (<6 months and >24 months). As in human transplanted heart, impairment of cardiovascular autonomic function may account for VEF decrease at rest in MS patients.…”
Section: Discussionmentioning
confidence: 97%
“…Human transplanted heart provides a good example of cardiac autonomic dysfunction. Some authors have found a significant decrease in left VEF in patients as compared with healthy control subjects (Verani et al ., 1994) or during the long‐term course after heart transplantation (Hartmann et al ., 1993) (<6 months and >24 months). As in human transplanted heart, impairment of cardiovascular autonomic function may account for VEF decrease at rest in MS patients.…”
Section: Discussionmentioning
confidence: 97%
“…Die notwendige Erhöhung der linksventrikulären Auswurfleistung erfolgt daher über eine Z u n a h m e des Schlagvolumens (2). Weitere Faktoren der insgesamt reduzierten linksventrikulären Leistung sind diastolische Funktionsstörungen (13,14,15,42,50), rezidivierende Abstoßungsreaktionen, Zyklosporinassoziierte Hypertension sowie immunsuppressiv bedingte interstitielle Fibrose (17,31) und Koronarsklerose (36,46). Trotz limitierter Leistungsreserve verbessert sich bei transplantierten Patienten im Laufe der Zeit die Frequenzadaptation unter Belastung (28), was auf eine sympathische Reinnervation hinweist (3).…”
unclassified